3D Printing: Helical 3D‐Printed Metal Electrodes as Custom‐Shaped 3D Platform for Electrochemical Devices (Adv. Funct. Mater. 5/2016). (February 2016) - Ambrosi, Adriano; Moo, James Guo Sheng; Pumera, Martin
Abstract : On page 698, A. Ambrosi, J. G. S. Moo, and M. Pumera show the use of metal 3D printing to fabricate bespoke electrochemical stainless steel electrodes that can be used as platform for different electrochemical applications ranging from electrochemical capacitors, oxygen evolution catalyst and pH sensor. The layer‐by‐layer printing is reflected in the layered structure of Antelope Canyon, Arizona, USA.